Low intensity laser therapy (LILT) in vivo acts on the neutrophils recruitment and chemokines/cytokines levels in a model of acute pulmonary inflammation induced by aerosol of lipopolysaccharide from Escherichia coli in rat - de Lima, F. Mafra; Villaverde, A. B.; Salgado, M. A. [UNESP]; Castro-Faria-Neto, H. C.; Munin, E.; Albertini, R.; Aimbire, F. (Elsevier B.V. Sa, 2010)
It has been suggested that low intensity laser therapy (LILT) act, on pulmonary inflammation Thus we investigate in this work if LILT (650 nm 2 5 mW 31 2 mW/cm(2) 1 3 J/cm(2) laser spot size of 008 cm(2) and irradiation time of 42 s) can attenuate edema neutrophil recruitment and inflammatory mediators in acute lung inflammation Thirty-five male Wistar rats (n = 7 per group) were distributed in the following experimental groups control laser LPS LPS + laser and dexamethasone + LPS Airway inflammation was measured 4 h post-LPS challenge Pulmonary microvascular leakage was used for measuring pulmonary edema Bronchoalveolar lavage fluid (BALF) cellularity and myeloperoxidase (MPO) were used for measuring neutrophil recruitment and activation RT-PCR was performed in lung tissue to assess mRNA expression of tumor necrosis factor-alpha (INF-alpha) interleukin-1 beta (IL-1 beta) interleukin (IL-10) cytokine-induced neutrophil chemoattractant-1 (CINC-1) macrophage inflammatory protein-2 (MIP-2) and intercellular adhesion molecule-1 (ICAM-1) Protein levels in both BALF and lung were determined by ELISA LILT inhibited pulmonary edema and endothelial cytoskeleton damage as well as neutrophil influx and activation Similarly the LILT reduced the INF-alpha and IL-1 beta in lung and BALF LILT prevented lung ICAM-1 up-regulation The rise of CINC-1 and MIP-2 protein levels in both lung and BALF and the lung mRNA expressions for IL-10 were unaffected Data suggest that the LILT effect is due to the inhibition of ICAM-1 via the inhibition of INF-alpha and IL-1 beta (C) 2010 Elsevier B V All rights reserved
Keywords: Pulmonary inflammation; Neutrophils; Inflammatory mediators; Endothelial cytoskeleton; Low intensity laser therapy